Understanding James Welch - McFarland, Ronald E. (Understanding contemporary American literature., 2000)
"In Understanding James Welch, Ron McFarland offers analysis and critical commentary on the works of the renowned Blackfoot-Gros Ventre writer whose first novel, Winter in the Blood, has become a classic in Native American fiction and whose book of poems, Riding the Earthboy 40, has remained in print since its initial publication in 1971. McFarland offers close readings of Welch's poems, four novels, and recent book, Killing Custer, which tells the story of the Battle of the Little Bighorn from a Native American perspective."--Jacket